Improved Cascaded H-Bridge Multilevel Inverters with Voltage-Boosting Capability - Sze Sing Lee (MDPI AG, 2021)
This paper proposes two improved cascaded H-bridge (ICHB) multilevel inverters that feature voltage-boosting capability. The conventional H-bridge with a front-end dc–dc boost converter was restructured for single-stage operation. The developed three-level topology not only saves one power switch but also exhibits lower voltage stress across its capacitor. Extension to five-level generation was also introduced by merely adding two power switches and one capacitor. The final five-level topology outperforms the classical cascaded H-bridge (CHB) multilevel inverter with a significant reduction in the power switch count, with a 42% and 50% reduction in both the isolated dc source and inductor counts. The power efficiency was also improved without compromising the modularity feature of the classical CHB multilevel inverter. The operation and theoretical analysis of the proposed topologies were validated via simulations and experimental tests.